Herbicide Adjuvants in Citrus Weed Control - Kanissery, Ramdas (EDIS, 2022)
Adjuvants are materials added into a herbicide spray mix that improves the herbicide’s performance, especially its handling, application efficacy, and crop-safety. Examples of adjuvants include surfactants, drift control agents, buffering agents, etc. For instance, surfactants (surface active agents) are an adjuvant designed for improving the coverage, foliar retention, and penetration of a herbicide spray mixture. This article will discuss various types of adjuvants and their utility in enhancing weed control efficacy and tree-safety in citrus weed management.